Peripheral ossifying fibroma/ossifying fibrous epulis - Zain, R.B.; Janakarajah, N. (1988)
This is a case report of a reactive lesion which occurs only in the gingiva. This lesion is of a long duration causing erosion of the superficial bone. Histologically it is similar to other epulides of the gingiva but in addition contains ossified tissue. The lesion's confusing terminology is being discussed in view of its understanding to an American-trained or a British-trained surgeon. A review of literature showed a recurrence rate of 7-20 thus making it mandatory for a close follow-up of the patient.